1995
DOI: 10.1007/bf00200407
|View full text |Cite
|
Sign up to set email alerts
|

MRI for evaluation of perianal inflammation

Abstract: In patients with known fistulas, MRI may determine the lesion's anatomic extent, localize unsuspected fistulas, and confirm or exclude the inflammation of the fistulous tract(s). Information obtained by MRI examination may, in turn, be used to determine treatment of patients with perirectal inflammatory lesions and can be a useful adjunct in following results of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…MRI was first performed with a body coil or external surface coil with reported accuracies up to 92%, but later studies have recorded lower values [3][4][5][15][16][17]. A major advance was the introduction of MRI with high spatial resolution using endoluminal or phased array coils.…”
Section: Discussionmentioning
confidence: 99%
“…MRI was first performed with a body coil or external surface coil with reported accuracies up to 92%, but later studies have recorded lower values [3][4][5][15][16][17]. A major advance was the introduction of MRI with high spatial resolution using endoluminal or phased array coils.…”
Section: Discussionmentioning
confidence: 99%
“…Multiplanar views clarify differentiation of supralevator from infralevator lesions. 97 MRI has been shown to be valuable in identification of the primary track as well as the presence, position, and course of secondary extensions. A prospective study comparing MR findings with blinded operative findings showed concordance of 86% for the presence and course of primary track, 91% for the presence and site of secondary extension or abscess, and 97% for the presence of horseshoeing.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Over the last years, two specialized imaging techniques have gained increasing value for the visualization of perianal fistulae: anal endosonography (AES) (3, 4) and magnetic resonance imaging (MRI). Both methods have been shown to be able to depict the courses of superficial and deep fistulae and their relation to anatomical landmarks (5–11). At our institution, these two modalities have been part of the diagnostic work‐up of patients with complex perianal disease.…”
mentioning
confidence: 99%